The Activities of Lithuanian Women during the Years of 1988–1992: Challenges and Opportunities - Jurėnienė, Virginija; Ibianskienė, Justė (Information & Media, 2018)
[full article and abstract in Lithuanian; abstract in English]This article studies the activities and the societal role of Lithuanian women during the years of 1988 to 1992 based on the relevant periodic press and the memoirs of contemporaries. An analysis of certain organizations, such as the gathering of Catholic women “Caritas,” the Lithuanian Women’s Movement, the Women’s Revival Union, the Lithuanian Women’s Union, the Women’s Union of the Families of the Officers of Lithuanian Grand Duchess Birutė and the Lithuanian University Women Association, presented an overview of the activities of organizations from 1988 to 1992. The article assesses the circumstances of the inception of the aforementioned organizations, their benefits to society and their value both to the participants and to the public.
Keywords: women’s organizat; Reform Movement of Lithuania; women’s activity